2018
DOI: 10.2174/1567205014666170921122458
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Metabolic and Synaptic Dysfunction Hypotheses of Alzheimer's Disease (AD): A Meta-Analysis of CSF Markers

Abstract: Background:Alzheimer’s disease (AD) is currently incurable and a majority of investigational drugs have failed clinical trials. One explanation for this failure may be the invalidity of hypotheses focus-ing on amyloid to explain AD pathogenesis. Recently, hypotheses which are centered on synaptic and met-abolic dysfunction are increasingly implicated in AD.Objective:Evaluate AD hypotheses by comparing neurotransmitter and metabolite marker concentrations in normal versus AD CSF.Methods:Meta-analysis allows for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 139 publications
(143 reference statements)
1
27
0
Order By: Relevance
“…The dual targeting of VEGFA and Ang2 was shown previously to increase M2 to M1-like skewing, which is indicative of a proinflammatory macrophage activation (22,24,25). In other studies, durable antitumor responses observed upon combining CD40 agonism with anti-CSF1R antibodies (36) or small-molecule CSF1R inhibitors (37,48) were attributed to the reduction of immunosuppressive M2-like TAMs and the simultaneous induction of polyfunctional inflammatory M1-like TAMs producing TNFα, IL-6, and IL-12. In our study, we observed a more pronounced effect on TAM depletion after anti-CD40 therapy in MC38 tumors compared to others (36).…”
Section: Discussionmentioning
confidence: 82%
“…The dual targeting of VEGFA and Ang2 was shown previously to increase M2 to M1-like skewing, which is indicative of a proinflammatory macrophage activation (22,24,25). In other studies, durable antitumor responses observed upon combining CD40 agonism with anti-CSF1R antibodies (36) or small-molecule CSF1R inhibitors (37,48) were attributed to the reduction of immunosuppressive M2-like TAMs and the simultaneous induction of polyfunctional inflammatory M1-like TAMs producing TNFα, IL-6, and IL-12. In our study, we observed a more pronounced effect on TAM depletion after anti-CD40 therapy in MC38 tumors compared to others (36).…”
Section: Discussionmentioning
confidence: 82%
“…al [63] found that increasing CLPTM1 levels decreased miniature inhibitory postsynaptic potentials, while reciprocally, decreasing CLPTM1 levels elevated GABA currents in the post-synaptic neuron, strongly suggesting that CLPTM1 negatively regulates GABAergic signaling. A recent literature meta-analysis looking at neurotransmitter synaptic dysregulation in AD, found decreased levels GABA in AD patients, supporting the potential dysregulation of GABAergic signaling in AD [65] Far less is known about CEACAM19, and any biological connection to AD. What work has been done is predominantly focused upon oncology.…”
Section: Apoc1 -Ceacam19 -Clptm1 Chr19mentioning
confidence: 97%
“…Some authors reported higher CSF glutamate values in AD patients than in controls [42,43], whereas others reported decreased values [44,45] or no changes at all [46][47][48]. A recent study using C13-glutamine performed in APP/PS1 mice suggests that reduced glutamine uptake and impaired oxidative glutamine metabolism could be very early markers of AD pathogenesis, as they precede the amyloid plaque formation in this model [49]. This hypothesis may be plausible in the rTg4510 mouse of the AD model at an early pathological stage.…”
Section: Discussionmentioning
confidence: 87%